Photodegradation of natural dye for solar application / Muhamad Nazirul Ibrahim - Ibrahim, Muhamad Nazirul (2023)
Due to its availability, purity, and diversity, solar energy is one of the most potential alternative energy sources. It is also among the absolute cheapest sources of energy. Some of the popular varieties of solar cells used in the process of gathering solar energy include organic dye solar cells, hybrid solar cells, non-crystal, multiple crystal, and single crystal silicon solar cells. Natural dyes are preferred over other colourants because they are less hazardous to the environment, more hygienic, easier to apply, and last longer. Any catalytic process that uses light is referred to as a photocatalytic process, and degradation of a particle that is accomplished using a catalyst while being affected by light is referred to as a photocatalytic degradation. The study used bougainvillaea flowers because they were simple to find and collect. This research was to investigate the potential of natural dye being used in solar energy applications, observe the colour variations of the natural dye following exposure to UV light during the process of photodegradation for a week and to study the potential of metal oxide to help the natural dye degradation process and for applications involving solar energy. The conductivity of natural dye was increase after doped with MgO and exposed to sunlight from 7.40 to 12.65. The colour of natural dye also changed after exposed to solar which was from dark brown to light brown. It was discovered that one alternate way for solar application can be the photodegradation of natural dye. This can take the place of synthetic dye, which pollutes the environment by contaminating the water. The colour of natural dye changed after being exposed to sunlight with the help of magnesium oxide, which made this study successful.